CT raw data (DICOM format) of coral mound core GeoB16313-2 from the Campeche coral mound province, MARIA S. MERIAN cruise MSM20-4 - Jürgen Titschack; Christian Timann; Arne-Jörn Lemke (PANGAEA, 2025)
Archive halves of gravity core GeoB16313-2 from a cold-water coral mound in the Campeche coral mound province, Gulf of Mexico, were scanned using a Toshiba Aquilion 64™ computer tomograph (CT) at the hospital Klinikum Bremen-Mitte, Germany, with an X-ray source voltage of 120 kV and a current of 600 mA. The CT image stacks have a resolution of 0.35 mm in the x and y directions and 0.5 mm resolution in the z direction (0.3 mm reconstruction interval). Images were reconstructed using Toshiba extquotesingles patented helical cone beam reconstruction technique (TCOT).